2008
DOI: 10.1186/1476-9255-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Topical anti-inflammatory activity of Polygonum cuspidatum extract in the TPA model of mouse ear inflammation

Abstract: Background: This study tested the ability of a characterized extract of Polygonum cuspidatum (PCE) to inhibit mouse ear inflammation in response to topical application of 12-Otetradecanoylphorbol-13-acetate (TPA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 44 publications
4
82
0
Order By: Relevance
“…Medicinal plants have been identified as a safe and effective alternative for the treatment of dermatological inflammatory diseases, replacing conventional drugs such as corticosteroids and nonsteroidal anti-inflammatory drugs (Bralley et al 2008;Maldini et al 2009;Cesca et al 2012). In this study, we identified polar compounds in S. trilobata hydroethanolic extract and also developed a new topical phytomedicine based on KA content with significant anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 98%
“…Medicinal plants have been identified as a safe and effective alternative for the treatment of dermatological inflammatory diseases, replacing conventional drugs such as corticosteroids and nonsteroidal anti-inflammatory drugs (Bralley et al 2008;Maldini et al 2009;Cesca et al 2012). In this study, we identified polar compounds in S. trilobata hydroethanolic extract and also developed a new topical phytomedicine based on KA content with significant anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Japanese knotweed (Polygonum cuspidatum) is used as an analgesic, antipyretic, diuretic and expectorant remedy in traditional Chinese medicine; anti-inflammatory properties, such as the inhibition of NF-B, have also been reported for this plant [31]. Indeed, interest in Japanese knotweed has increased due to the high concentration of resveratrol and its glycosides in the roots.…”
Section: Resultsmentioning
confidence: 99%
“…33 Bralley et al reported that grape phenolic components inhibit inflammation, edema, and white blood infiltration in mice induced with 12-O-tetra decanoylphorbol 13-acetate. 34 Additionally, this component shows comparable effects to indomethacin, a widely used medication for degenerative joint diseases. 35 These observations demonstrate that resveratrol has clear anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%